Srategi Eddy Azwar dan Selamat di Pilkada Kabupaten Deli Serdang - FEBRIANI, REZKA (Politeia: Jurnal Ilmu Politik, 2015)
Direct local elections in accordance with law No. 32 of 2004 is a democratic process in Indonesia. Local elections is very important in the development of democracy. With the local elections, the people can exercise their right to choose their political leaders in the region. This is a the study of the regional election through independent pathways in Deli Serdang. This is study about Analysis of Eddy Azwar â Selamat Strategy. The finding is there are four strategies used by Eddy Azwar â Selamat in the process of the Local Election 2013 in Kabupaten Deli Serdang. First make the methods of research or survey before preparing and carrying out cam-paign activities. Second, prepare the campaign plan. Third, evaluate the progress of campaign report. Fourth,implement newa campaign. The method used is descriptive - qualitative method. This study is using political marketing as the approach and the data collection is using field research.Keywords: Strategy, elections of regional heads, Independent.